ANALISIS DAN STRATEGI PENGEMBANGAN USAHATANI SAYURAN PRIMA DI KOTA SAMARINDA (Analysis and Development Strategy of Prima Vegetable Farming in Samarinda City) - DANIEL MUTAQQIEN; SITI BALKIS; MURSIDAH MURSIDAH (Universitas Mulawarman (University of Mulawarman), 2018)
The aims of this research were to know (1) the production cost and farmer income from prima vegetable farming (2) the (R/C) prima vegetable farming ratio, (3) the internal and external factors which are influential towards prima vegetable farming. This research was conducted from March to Mei 2017, at Samarinda City, Districts of North Samarinda and Loa Janan Ilir. The subjects of this research were the farmers who had certificate of Prima 3 from OKKPD of East Borneo Province. The methods of data analysis are cost and profit, R/C ratio, and SWOT analysis. The average of production cost was IDR48,301,444.74 cropping season (cs)-1 ha-1 and the average of revenue was IDR14,000,000.00 cs-1 or IDR88,888,888.89 cs-1 ha-1. The average of profit was IDR6,443,647.45 cs-1 or IDR40,587,444.15 cs-1 ha-1. The R/C ratio was 1.84 that meant prima vegetable could be developed because the R/C > 1. Agresive strategy could be used to develop the prime vegetable farming.